Religious Moderation and Deradicalization in Indonesian Higher Education: A Case Study of ITB and IPB - Fahrudin, Ali; Nasrulloh, Nasrulloh; Suhadak, Faridatus; Haris, Abdul; Kholqi, A.M. Sa’dul (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2024)
This study aims to determine the internalization of religious moderation among Muslim students at ITB and IPB and its implications for the deradicalization movement in Indonesia. There are four main pillars that indicate national commitment: tolerance, non-violence, and respect for local traditions and culture. Two important factors motivated the writing of this article: first, the suspicion that radicalism occurs among students, and second, the belief that most radicalism occurs on non-religious campuses due to a lack of understanding of Islamic religious sources. Are these assumptions true? Therefore, this research was conducted on the campuses of ITB and IPB, which are well-known non-religious campuses in Indonesia. This research employed a qualitative method with a phenomenological approach, collecting data through in-depth interviews. The study concluded that the internalization of moderation at IPB and ITB is very good, drawing insights from various sources including the campus environment, social media, several studies, and the broader community. Students at both campuses generally exhibit a moderate attitude, although some students' understanding of moderation is not yet fully developed. For example, when asked to choose a president, 45% of students chose a Muslim candidate, while 40% based their choice on justice and skills rather than religion. Based on the moderate attitudes of students at both universities, the behavior of religious radicalism is unlikely to occur or even exist. Thus, students on both campuses are considered to have implemented the four main pillars of religious moderation.